2018
DOI: 10.1186/s12974-018-1227-0
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and blood-brain barrier breach remote from the primary injury following neurotrauma

Abstract: BackgroundFollowing injury to the central nervous system, increased microglia, secretion of pro- and anti-inflammatory cytokines, and altered blood-brain barrier permeability, a hallmark of degeneration, are observed at and immediately adjacent to the injury site. However, few studies investigate how regions remote from the primary injury could also suffer from inflammation and secondary degeneration.MethodsAdult female Piebald-Viral-Glaxo (PVG) rats underwent partial transection of the right optic nerve, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
5
16
0
Order By: Relevance
“…Secondly, CD68 was used in this study and Iba-1 was used in the previous study. These two different antibodies may not label exactly the same number or category of microglia/ macrophages because not all CD68 positive cells are positive for Iba-1, a point that has been shown in different studies 11 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Secondly, CD68 was used in this study and Iba-1 was used in the previous study. These two different antibodies may not label exactly the same number or category of microglia/ macrophages because not all CD68 positive cells are positive for Iba-1, a point that has been shown in different studies 11 .…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have used this model [4][5][6][7][8][9][10][11][12][13] . In these previous studies, PONT in rats was administrated from the superior side of optic nerves; however, in this study we cut the optic nerves from the temporal side and found that this operation was much easier to conduct than from the superior side due to the lack of obstruction from rectus superior and obliquus superior eye muscles ( Fig.…”
Section: Glaucoma and Partial Optic Nerve Transection Modelmentioning
confidence: 99%
“…However, it is increasingly understood that these markers can be co‐expressed and increased in the same cells following injury (Smith et al . ), and are therefore not definitive indicators of pro‐ or anti‐inflammatory events.…”
Section: Discussionmentioning
confidence: 99%
“…Non-specific binding sites were blocked with 10% goat serum in PBS for 30 min. Sections were then incubated with goat anti-mouse IgG conjugated with Alexa 488 fluorophore (1:200, Invitrogen, USA) at 4 • C for 20 h. Sections were then washed with PBS before application of The expression of ionized calcium-binding adaptor protein-1 (Iba-1) was determined as a measure of neuroinflammation by indicating microglial recruitment, as described previously (19). Twenty Micrometer thick cryosections of the right brain hemispheres were incubated in Tris-EDTA (T.E) buffer (10 mM, pH 6.0) for 20 h at 37 • C for antigen retrieval.…”
Section: -Dimensional Assessment Of Blood-brain Barrier Integrity Anmentioning
confidence: 99%